2018
DOI: 10.5271/sjweh.3772
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of work and lifestyle factors to socioeconomic inequalities in self-rated health ‒ a systematic review

Abstract: The contribution of work and lifestyle factors to socioeconomic inequalities in self-rated health-a systematic review by Dieker ACM, IJzelenberg W, Proper KI, Burdorf A, Ket JCF, van der Beek AJ, Hulsegge G This study is the first systematic review on the contribution of work and lifestyle factors to socioeconomic inequalities in perceived health among workers. Work and lifestyle factors partly explained socioeconomic health inequalities. This has important implications for public and occupational health polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 51 publications
(129 reference statements)
2
66
1
Order By: Relevance
“…Poor health is a prerequisite for receiving disability benefits and the educational differences in years with disability benefits reflect educational inequalities in health (28), as well as in strenuous working conditions and unhealthy behaviors. Our results concerning educational inequalities in working years lost due to disability benefits are in line with a recent Finnish study showing that the highest educated men lost 0.6 years due to disability retirement compared to 2.7 years among the lowest educated group.…”
Section: Discussionmentioning
confidence: 99%
“…Poor health is a prerequisite for receiving disability benefits and the educational differences in years with disability benefits reflect educational inequalities in health (28), as well as in strenuous working conditions and unhealthy behaviors. Our results concerning educational inequalities in working years lost due to disability benefits are in line with a recent Finnish study showing that the highest educated men lost 0.6 years due to disability retirement compared to 2.7 years among the lowest educated group.…”
Section: Discussionmentioning
confidence: 99%
“…Such other factors may, for example, involve socio-economic, cultural, health-related or work-related factors. 3 Some of these, such as age, psychosocial risk factors (eg, job strain, social support, job security), and other health behaviors were controlled for in our mediation model and did not appear to influence the effect substantially. Still, some other factors could play a confounding or explanatory role, such as socio-economic or cultural aspects, but were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…2 Among workers, lifestyle and physical and psychosocial work factors have been identified as important determinants of inequalities in self-rated health. 3 To improve the health of lower SEP workers, knowledge about the determinants and the interplay between them is important.…”
mentioning
confidence: 99%
“…The behavioral domain includes unhealthy behavior, such as substance use, lack of physical activity and poor dietary habits [28]. A systematic review by Dieker et al [29] showed that physical and psychosocial work factors explained approximately one-third of the socioeconomic inequalities in self-rated health, irrespective of lifestyle, which explained approximately one-fifth of the socioeconomic inequalities in self-rated health.…”
Section: Public Health Implicationsmentioning
confidence: 99%